Human Resources Strategies & Lessons Learned During the COVID-19 Pandemic: A Literature Review - Queenie C. PLATER; Marquise D. FRAZIER; Patricia Y. TALBERT; Vivian H. DAVIS; Payton S. TALBERT (Management Dynamics in the Knowledge Economy, 2022)
The novel coronavirus (COVID-19) pandemic has been the most devastating public health crisis since the Spanish flu pandemic of 1918-1920. COVID-19 has impacted every human being and operational system throughout the land. The pandemic has caused challenging times for businesses, financial markets, government agencies, and academia. One area frequently overlooked is COVID-19’s impact implications for workplaces, working practices, and Human Resource Management (HRM) operationalization. This literature review aims to identify best practices implemented for the sustainability of Human Resources (HR) functions and the survival of institutions in the age of a dynamic public health crisis. This is an effective approach to better understand the disruptions caused by COVID-19 on HRM and examine how this pandemic has impacted organizations. The findings obtained focus on four main pillars: (1) recruitment, retention, and the Great Resignation, (2) employee well-being and wellness, (3) remote work options, practices, and professionalism, and (4) HR practitioners' leadership development. These have continued to be salient themes interwoven throughout many articles. These findings suggest that talent and having the most experienced, operationalized, and professional individuals as part of one’s organization are paramount to its success. Upskilling is imperative, and all stakeholders must be open to the inevitability of change as change is constant.